PENYULUHAN KONSUMSI JUS JAMBU BIJI UNTUK MENINGKATKAN KADAR HEMOGLOBIN IBU HAMIL - sihaloho, wilfa muslimah (Jurnal Pengabdian Masyarakat Putri Hijau, 2023)
Anemia in pregnant women is a problem that can threaten the condition of the mother and fetus in the mother's womb. Anemia in pregnancy is a very global problem. Judging by the magnitude of the problem, anemia is the second leading worldwide cause of disability and thus a serious public health problem. The purpose of this study was to determine the effect of consumption of guava juice on increasing hemoglobin levels in third trimester pregnant women at the Citra Marendal Maternity Clinic in 2023. This research method used the Pre and Post Test Control One Group Design design, namely to determine the effect of differences in giving guava juice (Psidium Guajava) L) before and after administration. The location of this research was at the Citra Marendal Maternity Clinic in Oktober-November 2023. It can be seen that the average increase in hemoglobin levels of pregnant women before guava juice. From the results, it can be concluded that there is an effect of consuming guava juice on increasing hemoglobin levels in third trimester pregnant women at the Citra Marendal Maternity Clinic.